2017
DOI: 10.1590/1518-8345.2143.2952
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of a nursing care protocol in anesthesia

Abstract: Objective:To construct and validate a nursing care protocol in anesthesia. Method:methodological study of face and content validation, judging clarity, relevance, pertinence and comprehensiveness of a care protocol, elaborated from the integrative review of previous literature and based on the conceptual model of assistance perioperative nursing of Castellanos and Jouclas. The protocol was evaluated by five anesthesiologists and nurses from the surgical center. The results were analyzed through the content val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
12

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 31 publications
0
16
0
12
Order By: Relevance
“…From reading the articles, data emerged concerning protocol creation. All articles mention the literature review as part of protocol creation, be it a simple or structured literature review, such as integrative (12)(13)(14)(15) and systematic (16)(17) reviews, with emphasis on scoping reviews (4,6) . In some articles, literature review is associated with another type of data collection, such as interviews (18)(19)(20)(21) and group discussions (22)(23)(24) .…”
Section: Resultsmentioning
confidence: 99%
“…From reading the articles, data emerged concerning protocol creation. All articles mention the literature review as part of protocol creation, be it a simple or structured literature review, such as integrative (12)(13)(14)(15) and systematic (16)(17) reviews, with emphasis on scoping reviews (4,6) . In some articles, literature review is associated with another type of data collection, such as interviews (18)(19)(20)(21) and group discussions (22)(23)(24) .…”
Section: Resultsmentioning
confidence: 99%
“…A study of construction and validation of a nursing care protocol in anesthesia (10) showed that the use of protocols and checklists can help in the detection of errors and negligence in relation to care through proper verification of equipment and materials. The study also shows that its use promote the exchange of information among professionals about the clinical conditions of the patient, which improves their perception about teamwork and prevents harm -aspects which contribute to patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…In this meander, the assistance protocols provide for the definition of a specific situation of assistence or care, describing details about the operational actions and specifications about the mode of execution and the professional executor. Thus, the protocols are justified because they are instruments that reduce the variability of conduct among professionals involved in health care, favor greater patient and professional safety, besides allowing the elaboration of process and results indicators, improving the quality of assistance (9)(10) .…”
Section: Introductionmentioning
confidence: 99%
“…Agregam aumento na segurança para o paciente e para o profissional; e auxiliam na tomada de decisão e na incorporação de novas tecnologias 11 . Possuem, também, como objetivo, favorecer a elaboração de indicadores de processos e resultados, aperfeiçoando a qualidade do atendimento 12 .…”
Section: Referencial Teóricounclassified